1998
DOI: 10.1172/jci1403
|View full text |Cite
|
Sign up to set email alerts
|

A missense mutation in hepatocyte nuclear factor-4 alpha, resulting in a reduced transactivation activity, in human late-onset non-insulin-dependent diabetes mellitus.

Abstract: Non-insulin-dependent diabetes mellitus (NIDDM) is a heterogeneous disorder characterized by hyperglycemia resulting from defects in insulin secretion and action. Recent studies have found mutations in the hepatocyte nuclear factor-4 alpha gene (HNF-4alpha) in families with maturity-onset diabetes of the young (MODY), an autosomal dominant form of diabetes characterized by early age at onset and a defect in glucose-stimulated insulin secretion. During the course of our search for susceptibility genes contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
76
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 36 publications
6
76
0
Order By: Relevance
“…Moreover, the two crucial regulatory TFs regulating hepatic lipogenesis, Srebp1 and Chrebp1, are also targets of Hnf4a, demonstrated by other groups and this study, respectively (22). Reduced levels of Hnf4a have been implicated in the pathogenesis of type 2 diabetes mellitus and type 1 form of maturity-onset diabetes of the young (13,(23)(24)(25)(26). The large number of hepatic genes affected by the misregulation of Hnf4a is thought to cause the impaired insulin signaling in these metabolic syndromes (20).…”
Section: Discussionmentioning
confidence: 57%
“…Moreover, the two crucial regulatory TFs regulating hepatic lipogenesis, Srebp1 and Chrebp1, are also targets of Hnf4a, demonstrated by other groups and this study, respectively (22). Reduced levels of Hnf4a have been implicated in the pathogenesis of type 2 diabetes mellitus and type 1 form of maturity-onset diabetes of the young (13,(23)(24)(25)(26). The large number of hepatic genes affected by the misregulation of Hnf4a is thought to cause the impaired insulin signaling in these metabolic syndromes (20).…”
Section: Discussionmentioning
confidence: 57%
“…In contrast, the widespread polymorphism (Pro12Ala allele) is protective against T2D in Caucasians, but not in South Asians [9,27]. Similarly, different mutations in HNF4A or IPF1 can lead to either pancreatic agenesis (for homozygous dominant-negative frameshift mutation in IPF1), MODY (for heterozygous dominant-negative frameshift mutation in IPF1, or loss of function mutation in HNF4A), or late-onset diabetes (for missense mutations in IPF1 or HNF4A) [28][29][30]. Studies examining prediabetic glycemic traits (fasting insulin, fasting glucose, glucose, and insulin levels after glucose challenge) have identified that loci implicated in T2D susceptibility can also harbor variants that correlate with continuous glycemic traits.…”
Section: Finding the Genetic Determinants Of Common Type 2 Diabetes -mentioning
confidence: 99%
“…This region includes a major positional candidate, the transcription factor hepatocyte nuclear factor (HNF)-4α gene whose coding mutations cause MODY1 [4] and more rarely familial monogenic late-onset type 2 diabetes [5]. In both cases, defective insulin secretion was shown in diabetic and not yet diabetic mutation carriers.…”
Section: Introductionmentioning
confidence: 99%